2017
DOI: 10.1080/10520295.2016.1185668
|View full text |Cite
|
Sign up to set email alerts
|

Lectin histochemistry for detecting cadmium-induced changes in the glycosylation pattern of rat placenta

Abstract: Cadmium (Cd) is an industrial and environmental pollutant that produces toxic effects on gametogenesis, pre- and post-implantation embryos, and the placenta. Because the effects of acute Cd intoxication on the placenta are not well understood, we investigated changes in its glycosylated components in Cd treated dams at days 4, 7, 10 and 15 of gestation using lectin histochemistry. CdCl was administered to pregnant rats; control animals received sterile normal saline. Placentas were processed for DBA, Con A, SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Arachis hypogaea what was available in the bibliography (Bulmer & Peel, 1996;Díaz et al, 2017;Dorsch et al, 2019;Fernández et al, 2000Fernández et al, , 2014Fiorentino et al, 2018;Jones et al, 1995Jones et al, , 1997Jones et al, , 2007Jones et al, , 2014Jones et al, , 2016Jones & Aplin, 2009;Munson et al, 1989;Sandoval et al, 2001;Stewart et al, 2000;Sgambati et al, 2002;Tatsuzuki et al, 2009) and from our observations in L. maximus. We used a tree based on the taxon-rich and well-resolved phylogeny of Placentalia (O'Leary et al, 2013) combined with a more comprehensively sampled phylogeny of Rodentia (Fabre et al, 2015).…”
Section: Lectin Affinity Asupporting
confidence: 57%
See 2 more Smart Citations
“…Arachis hypogaea what was available in the bibliography (Bulmer & Peel, 1996;Díaz et al, 2017;Dorsch et al, 2019;Fernández et al, 2000Fernández et al, , 2014Fiorentino et al, 2018;Jones et al, 1995Jones et al, , 1997Jones et al, , 2007Jones et al, , 2014Jones et al, , 2016Jones & Aplin, 2009;Munson et al, 1989;Sandoval et al, 2001;Stewart et al, 2000;Sgambati et al, 2002;Tatsuzuki et al, 2009) and from our observations in L. maximus. We used a tree based on the taxon-rich and well-resolved phylogeny of Placentalia (O'Leary et al, 2013) combined with a more comprehensively sampled phylogeny of Rodentia (Fabre et al, 2015).…”
Section: Lectin Affinity Asupporting
confidence: 57%
“…On the other side, the alteration in the normal expression of some glycosidic residues of the placental glycotype could affect placental homeostasis, as well as embryonic growth and development, regardless of the type of placentation. This has been observed in Rattus norvegicus through variations in α and β-GalNAc, L-Fucose, α-D-Mannose, and α-D-Glucose (Díaz et al, 2017) and Bos taurus for variations in the expression of α-D-Mannose, NeuNac, and β-Gal (Dorsch et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Controls for lectin staining included: exposure to horseradish-peroxidase and substrate medium without lectin and blocking by incubation with the appropriate blocking sugars (0.1 to 0.2M in PBS) for 1 h at room temperature before applying to the sections. The intensity of lectin binding was subjectively scored from (-) (none) to +++ (strongly positive) following the system used previously (Fernández et al, 2014;Díaz et al, 2017). The structures studied in the lungs were glycocalix and cytoplasm of the epithelium of bronchi, bronchioli and alveoli and vascular endothelium.…”
Section: Concanavalia Ensiformismentioning
confidence: 99%
“…[25] Consistent with previous studies, our study indicated that Cd upregulates the expression of glucocorticoids. [26] Cd not only affects the hormone expression at the hypothalamo-pituitary-adrenal axis level, but also locally affects the expression of cortisol. [27] Glucocorticoids promotes fetal lung maturity, while the high concentration of glucocorticoids enters the fetus through the placenta barrier will affects fetal growth and development.…”
Section: Discussionmentioning
confidence: 99%